Proceedings of the Seventh International Workshop on Data Mining for Online Advertising 2013
DOI: 10.1145/2501040.2501980
|View full text |Cite
|
Sign up to set email alerts
|

Real-time bidding for online advertising

Abstract: The real-time bidding (RTB), aka programmatic buying, has recently become the fastest growing area in online advertising. Instead of bulking buying and inventory-centric buying, RTB mimics stock exchanges and utilises computer algorithms to automatically buy and sell ads in real-time; It uses per impression context and targets the ads to specific people based on data about them, and hence dramatically increases the effectiveness of display advertising. In this paper, we provide an empirical analysis and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
149
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(153 citation statements)
references
References 31 publications
(32 reference statements)
3
149
0
1
Order By: Relevance
“…It is particularly important to control the over spending as some of RTB auctions are in fact the first price auction or with soft floor prices [29]. Table 7 gives the statistics related to high bid prices, where the bid value exceeds the highest market price 300 in our dataset.…”
Section: Bidding Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is particularly important to control the over spending as some of RTB auctions are in fact the first price auction or with soft floor prices [29]. Table 7 gives the statistics related to high bid prices, where the bid value exceeds the highest market price 300 in our dataset.…”
Section: Bidding Data Analysismentioning
confidence: 99%
“…Note that in the second price auction, the game theoretical approach and the rational assumption lead to a truthful bidding, independent of market price [11]. However, empirical studies have shown that advertisers are quite often not rational in RTB [29] and in this paper, we take a stochastic approach by following [2].…”
Section: Introductionmentioning
confidence: 99%
“…Ad exchanges as well as search providers use Real-Time Bidding (RTB), which is a popular way of delivering online advertising, see [3,9,13,20]. As reported in [5], spending on RTB in the US during 2014 increased by 137% and reached $10 billion and RTB has 45% of the total spend in online advertising.…”
Section: Introductionmentioning
confidence: 99%
“…Marketing managers expect that online advertising brings customers at cheaper costs and granular targeting capabilities although the traditional offline advertisement is continued. In Figure 1 we show the scheme of the RTB system, which consists of 4 components: a user, a webpage with embedded ad place, demand partners (advertising platforms) and ad campaigns; see [17,20] for more detail.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, online advertising revenues in the United States were estimated to be $42.8 billion [2], an increase of 17% over the previous year. The increasing revenue stream of Web advertisement has given rise to another innovative part of the Web ecosystem: ad-sellers, ad-bidders, and ad-brokers-the adnetworks [10,59]. These parties negotiate placement of advertisements in today's Web.…”
Section: Introductionmentioning
confidence: 99%